Clinical Profile and Upper Gastrointestinal Endoscopic Findings in Patients with Dysphagia and Its Relation to Alarm Symptoms (British Journal of Multidisciplinary and Advanced Studies, 2023)
Dysphagia is derived from the Greek word dys (difficulty, disordered) and phagia (to eat). It refers to the sensation where food is hindered in its passage from the mouth to the stomach. It is of two types – Oropharyngeal and Esophageal. Esophageal dysphagia can be either motor or mechanical. Symptoms vary depending upon the degree of luminal obstruction, associated esophagitis and type of food taken.Study design: prospective cross sectional study . The study took place from November 2021 to December 2022 in Department of Gastroenterology, BSM Medical University, Dhaka Bangladesh with sample size of 125. Patients with dysphagia with or without alarm symptoms attending the outpatient clinic of Gastroenterology department during the period were selected for study. Results show that a total of 125 patients were included in the study, 63 males and 72 females. Majority of patients were seen in the age group of 41 – 60 yrs (43.7 %). Clinically significant weight loss and vomiting was seen in around 22.2 % of the patients. Endoscopy was done in all patients presented with dysphagia. The common cause of dysphagia among the malignant etiology was found to be Ca Oropharynx (12%), followed by Ca Esophagus (4.8%), Ca OG JN (2.4%). Among the benign causes the most common etiology was due to post cricoid web (12.8%), followed by esophageal strictures (12%). Endoscopy was found to be normal in 37 patients (29.6%). Malignant etiology was found to be more common among males. Normal endoscopy was predominant among females. In conclusion, Upper GI Endoscopy is virtually always needed in the evaluation of esophageal dysphagia, allows tissue sampling, and, in many cases, is therapeutic, obviating the need for further evaluation. It is a very effective and appropriate tool to diagnose the causes of dysphagia in both the young and especially the elderly. Alarm symptoms like anorexia, vomiting, wt loss, melena may be more suggestive of malignant cause. Upper GI endoscopy will help in making an early and definite diagnosis.